2009
DOI: 10.1038/onc.2009.15
|View full text |Cite
|
Sign up to set email alerts
|

EphrinA5 acts as a tumor suppressor in glioma by negative regulation of epidermal growth factor receptor

Abstract: Eph receptors, the largest subfamily of receptor tyrosine kinases, and their ephrin ligands play important roles in nervous system development. Recently, they have been implicated in tumorigenesis of different cancers. In this study, we showed that the expression of ephrinA5 was dramatically downregulated in primary gliomas compared with normal tissues. Forced expression of ephrinA5 reduced tumorigenicity of human glioma U373 cells. Epidermal growth factor receptor (EGFR), which frequently acts as an oncoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 36 publications
3
56
0
Order By: Relevance
“…Ephrin-B2 has also been implicated in the advancement of uterine endometrial, ovarian and cervical cancers [41,43,44]. By contrast, forced expression of ephrin-A5 suppressed tumor formation by U373 glioma cells through negative regulation of EGFR [34], while elevated expression of both ephrin-B2 and ephrin-B3 has been associated with suppression of the malignant phenotype of neuroblastoma [45,46].…”
Section: Tumorigenicitymentioning
confidence: 90%
See 2 more Smart Citations
“…Ephrin-B2 has also been implicated in the advancement of uterine endometrial, ovarian and cervical cancers [41,43,44]. By contrast, forced expression of ephrin-A5 suppressed tumor formation by U373 glioma cells through negative regulation of EGFR [34], while elevated expression of both ephrin-B2 and ephrin-B3 has been associated with suppression of the malignant phenotype of neuroblastoma [45,46].…”
Section: Tumorigenicitymentioning
confidence: 90%
“…Glioma RT-PCR ↓ Expression in GBM tissue (n = 23) compared with normal tissue (n = 5) [34] Ovarian Ephrin-A1, A4, B1 and B2 have been detected in vascular endothelium in a range of cancers, including breast, osteosarcoma, Kaposi's sarcoma and urinary bladder carcinoma, especially at the sites of tumor neovascularization [32,[61][62][63][64]. Furthermore, it has been demonstrated that activation of endothelial ephrin-B1 promoted neovascularization [65].…”
Section: Ephrin-a1mentioning
confidence: 98%
See 1 more Smart Citation
“…GLT1 and GLAST colocalize with ephrin-A3 on astrocyte processes, suggesting a functional crosstalk between these proteins that may depend on their physical proximity . Further studies are needed to determine if ephrin-A3 reverse signaling regulates glutamate transporters through activation of Src kinases and/or by ubiquitination and degradation (Baba et al, 2009;Davy and Robbins, 2000;Davy et al, 1999;Holen et al, 2008;Huai and Drescher, 2001;Li et al, 2009). A better understanding of ephrin-A3 reverse signaling pathways in astrocytes will likely provide important insight into the mechanisms regulating extracellular glutamate levels in the hippocampus.…”
Section: Ephrin-a3 Reverse Signaling In Astrocytesmentioning
confidence: 96%
“…Interestingly, they have been assigned both tumor promoter and suppressor functions in different cellular contexts [14][15][16][17][18][19]. As mentioned earlier, many of the functions regulated by Eph/Ephrin signaling are cell guidance functions directly reminiscent of the metastatic process.…”
Section: Introductionmentioning
confidence: 95%